Kualitas dan Interpretasi Hadis tentang Penghuni Surga dan Neraka: Study Takhrij dan Syarah Hadis - Kaka Reza Abdullah (Gunung Djati Conference Series, 2022)
This study aims to discuss the Hadith about the quality and interpretation of the Hadith about the number of women inhabiting heaven and hell. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about heaven and hell in Muslim's narration No. 4919. The results and discussion of this study show that the status of the hadith is hasan li ghairihi which meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the Hadith narrated by Muslim No. 4919 is relevant to be interpreted symbolically that women are not always physical but as well as the slander of women.